Who Benefits from the Food-for-School Program and Tindahan Natin Program: Lessons in Targeting - Rosario G. Manasan; Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2007)
The prevalence of hunger in the Philippines prompted the government to launch its hunger mitigation initiative in November 2005. The initiative consisted of two programs: the Food-for-School Program (FSP) and the Tindahan Natin Program (TNP). The FSP belongs to a class of social safety nets called conditional cash or in-kind transfers. There is a growing interest on these instruments worldwide because of evidence that they have not only been useful in providing assistance to poor families but more so because they have been found effective in securing investments in human capital among the poor. On the other hand, the TNP is a targeted food price subsidy program. Like other food price subsidy programs, it operates by lowering the price of certain food items. The lower food price effectively results in increased purchasing power that translates into an increase in the real income of beneficiaries. The budget allocation for these programs has been increasing in recent years. One interesting question to ask now is: Who benefits from the governments hunger mitigation program? The answer to this question has a large bearing on both the effectiveness and efficiency of the program. Given this perspective, the paper assesses the 1) distribution of the benefits from the FSP and TNP in 2006, and 2) implications on targeting of the use of public schools and day care centers as distribution points. In the process, it also draws some lessons in targeting.
Keywords: 330; targeting; Food-for-School Program (FSP); in-kind transfers; leakage rate; undercoverage rate; Tindahan Natin Program; hunger mitigation; food price subsidy; Conditional Cash Transfers (CCT); Ernährungssicherung; Ernährungspolitik; Philippinen